Analisis Perbaikan Sistem Pada Proses Penanganan Barang Berbahaya Guna Meminimalisir Terjadinya Insiden Barang Berbahaya Di Pt. XYZ Menggunakan Fault Tree Analysis Pada Tahun 2023 - Rizaldy, Wynd; Maulana, Andy; Abdurrazzaq, Ahsan Zaid (Jurnal Sistem Transportasi & Logistik, 2025)
Incidents related to hazardous goods can have serious impacts on safety, the environment, and a company's reputation. Therefore, effective and safe handling of hazardous goods is crucial for logistics companies. This research aims to analyze and improve the hazardous goods handling system at PT. XYZ with the goal of reducing the potential for incidents. In this study, the Fault Tree Analysis (FTA) method is used as the main analytical tool. The first step involves identifying potential incidents that could occur in the hazardous goods handling process. Then, the key causative factors of these incidents are determined through Fishbone. From here, these causative factors are further analyzed to identify weak points in the system that could lead to incidents. After identifying these weak points, the next step is to design improvement recommendations. These recommendations encompass improvements in operational procedures, workforce training, equipment maintenance, and supervision. It is hoped that implementing these recommendations will help decrease the risk of hazardous goods-related incidents at PT. XYZ. The results of this study provide in-depth insights into the hazardous goods handling system of the company. By utilizing the FTA analysis approach, this research offers a comprehensive view of potential causative factors and their interrelationships. This will serve as a foundation for the company to take better preventive actions and implement necessary improvements.